(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
This paper aims to explain systematic applied study of Talent Management (TM) and Knowledge Management (KM) assembly in an Information Technology (IT) industry in Pune, Maharashtra (India). Scope of research study compacts IT organizations in Pune, Maharashtra (India). This article kindles talent management and knowledge management connecting variables and its effectiveness in performance of 93 IT based firms situated at Pune. The employees who are working in organizations and creates their own creations with own talents are called as “Knowledge workers” also termed as “Talents” for an organization. These creation is shared, transformed , captured in organizational process for organizational strategies termed as “Knowledge” Catherine L Wang et.al (2003).The objectives of this research study is to study the concept of talent management and knowledge management and examines different aspects of its connecting variables and its performance efficiency in IT organizations. Findings of the study will help IT organizations to improve their Talent Management and Knowledge Management connecting process and factors to enhancing overall performance and effectiveness. Researcher provide Talent Management (TM) and Knowledge Management (KM) linking model on the basis of empirical analytical study.